Ancestral North: spirituality and cultural imagination in Nordic ritual folk music - Hagen, Ross (Extreme sounds studies, 2024)
Paradoxes of Ritual Folk Music : Enchantment and Escape -- Anglo Fascinations : A Cultural History of Borealism -- The Music of the North -- World Music of the Ancient World -- Individual Musical Approaches : Ancient Enchantments, Modern Technology, and Putting Away "Viking Things." -- Aftermath. Final Libations.